GREEN TRANSFORMATIONAL LEADERSHIP, GREEN HUMAN RESOURCE MANAGEMENT, AND ENVIRONMENTAL PERFORMANCE: A MEDIATION MODEL - Satriadi Satriadi; Tubel Agusven; Marhalinda Marhalinda; Imran Ilyas; Alex Zami (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study aims to determine the effect of the relationship between green transformational leadership and green human resource management on environmental performance mediated by green organizational culture and green work engagement. This study applied a survey method. Its population involve 236 respondents of manufacturing company managers in Indonesia. Data analysis uses PLS-SEM. The results of the study indicate that green transformational leadership and green HRM are positively and significantly related to environmental performance. Through mediation variables, this study reveals new findings that the green organizational culture variable does not significantly influence the relationship between green transformational leadership and environmental performance. This study reveals the complete mediation of green work engagement in the relationship between green human resource management and environmental performance. The current research provides valuable insights into green transformational leadership and green human resource management that can generate positive energy in manufacturing company managers in Indonesia.